Female Earnings Inequality: The Changing Role of Family Characteristics and Its Effect on the Extensive and Intensive Margins - Card, David; Hyslop, Dean R. (Journal of Labor Economics, 2021)
Using data for three cohorts of women in the PSID, we show that annual earnings inequality fell sharply between the late 1960s and the mid-1990s, with a large decline in the component attributable to the extensive margin. We then fit earnings-generating models that incorporate both intensive- and extensive-margin dynamics to data for the three cohorts. Our models suggest that more than 80% of the decline in female earnings inequality can be attributed to a weakening of the link between family-based factors (i.e., children and the presence and incomes of partners) and the intensive and extensive margins of earnings determination.